Konstruksi Sosial Stereotip Laki-Laki Feminin - Noer Khavifah; Fardiah Oktariani Lubis; Oky Oxcygentri (Peneliti.net, 2022)
Indonesian society has stereotypes that differentiate between men and women. Women are required to behave in a feminine manner, and men are required to behave in a masculine manner. Even though there have been stereotypes in society, in reality there are still men who have more dominant feminine traits or are referred to as feminine men. The existence of a feminine male is of course not in accordance with the behavior expected by society. The existence of this discrepancy resulted in a stigma as social control in society. The purpose of this study was to determine the views of feminine men on masculinity stereotypes and stereotypes as feminine men. This research method is qualitative with a case study approach with a multi-case design, data collection techniques with in-depth interviews, observation and documentation. The results of this study are feminine men view that the concept of masculinity which has been used as a standard to define a person as an ideal man and to conform to society's expectations, is still very rigid and still based on the values ​​of masculinity and strength and the view that This suggests that feminine men have a more fluid view when explaining the concept of masculinity. In choosing himself to be a feminine man, the feminine man in the results of this study still applies some existing masculinity values, but once again does not have to depend on or rely on the stereotypes that have been set by society